2022
DOI: 10.3390/healthcare10122435
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance, Psychological Distress and Perceived Burden in Female Family Caregivers of Dependent Patients with Dementia: A Case-Control Study

Abstract: This case-control study analyzed the sleep disturbance, psychological distress and perceived burden in female family caregivers of dependent people with dementia (n = 74) compared with female family caregivers of dependent people without dementia (n = 74) and with age-matched non-caregiver control females (n = 74). Participants completed the Pittsburgh Sleep Quality Index (PSQI), the 12-item General Health Questionnaire (GHQ-12), the Caregiver Burden Inventory (CBI) and an ad hoc questionnaire to collect socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…This could be because caregivers' sleep problems have an impact on the caregiving tasks they perform, as a result of lower concentration, more mistakes, and reduced patience, which increases caregivers' perception of burden. These results are consistent with those found in previous studies of caregiver populations using the PSQI [7,55] and an insomnia diagnostic interview [6]. On the other hand, a significant positive correlation was found between lower sleep quality and greater psychological distress, indicating a relationship between PSQI and possible mental health problems (anxiety and depression) in caregivers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be because caregivers' sleep problems have an impact on the caregiving tasks they perform, as a result of lower concentration, more mistakes, and reduced patience, which increases caregivers' perception of burden. These results are consistent with those found in previous studies of caregiver populations using the PSQI [7,55] and an insomnia diagnostic interview [6]. On the other hand, a significant positive correlation was found between lower sleep quality and greater psychological distress, indicating a relationship between PSQI and possible mental health problems (anxiety and depression) in caregivers.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, sleep disturbances are common among non-professional caregivers, often linked to the sleep disturbances or nighttime behaviors of the care recipient [5]. Previous studies have reported that 41.0% of caregivers experience insomnia [6] and 76.1% suffer from poor sleep quality [7]. Sleep quality refers to a complex construct that includes quantitative aspects of sleep such as sleep duration, sleep latency, and sleep efficiency, as well as subjective aspects, such as restfulness of sleep or daytime dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, neurodegenerative disorders affect not only patients but their entire households, especially the primary carer. Indeed, studies [13][14][15][16] have shown that approximately two-thirds of older adult caregivers have some form of sleep disturbance. Thus, early intervention of sleep disorders among older adults can improve their quality of life, reduce their risk of developing neurodegenerative disorders, and prevent further complications among household members.…”
Section: Overviewmentioning
confidence: 99%
“…Con el uso del Inventario SiSCo del Estrés Académico y de una ficha sociodemográfica, se pudieron determinar reacciones comunes en los niveles de estrés elevados que perjudican el rendimiento académico, el bienestar psicológico y la calidad de vida (Estrada et al, 2021). Simón et al (2022) destacan la importancia de llevar a cabo investigaciones en el ámbito internacional sobre la calidad de sueño y el estrés generados en la pandemia de covid-19 para comprender la magnitud del fenómeno, con el fin de crear intervenciones para mejorar la salud mental de la población. Además, la OMS (2022) indica que la promoción de la salud mental y del sueño saludable son de gran relevancia para mantener un equilibrio y bienestar en el desarrollo personal y comunitario.…”
Section: Artículos Originalesunclassified